Pengaruh Self Control Terhadap Toleransi Peserta Didik - Rosyada, Ananda Intan; Huda, Nurul (Sekolah Tinggi Agama Islam Pati, 2023)
The purpose of this research is to find out: 1) To find out the self control of students at MI I`anatul Athfal Cengkalsewu Sukolilo Pati in 2022. 2) To find out the tolerance of students at MI I`anatul Athfal Cengkalsewu Sukolilo Pati in 2022. 3) To determine the effect of self-control on students' tolerance at MI I`anatul Athfal Cengkalsewu Sukolilo Pati in 2022. The type of research used is research conducted in the field or field research. The approach used in this research is a quantitative approach. This research took 50% of the sample from the existing population. This research was conducted from 4 August to 4 September 2022. Data collection techniques were in the form of questionnaires and documentation. Meanwhile, the data analysis technique uses a simple regression formula. This research concludes: 1) The Self Control of students at MI I`anatul Athfal Cengkalsewu Sukolilo Pati in 2022, an average of 33.46, is in the good category, because it is in the interval 30 – 35. 2) The tolerance that exists in students at MI I`anatul Athfal Cengkalsewu Sukolilo Pati in 2022, the average score of 32.98 is in the good category, because it is in the interval 30 – 35. 3) There is an influence of self-control on the tolerance of students at MI I `anatul Athfal Cengkalsewu Sukolilo Pati 2022. This is shown from the results of the questionnaire calculation of = 1.521, which is a value greater than rtable = 0.2181 for a significance level of 5%. Meanwhile, at the 1% significance level for respondents totaling N = 58, we get rtable = (df = N - 2) namely (58 – 2 = 56) meaning rtable = 0.2181 while rcount = 1.521 which means rcount is greater than rtable (rcount rtable). Thus, at the 1% significance level, the results are significant, which means there is a correlation between the two variables. This shows that rcount is significant.